Molecular epidemiology of Streptococcus pneumoniae with decreased susceptibility to penicillin in a Paris children's hospital. - Moissenet, D (1997)
Among pneumococci with decreased susceptibility or pneumococci resistant to penicillin (PRP) isolated at Armand-Trousseau children's hospital, those expressing capsular serotypes 23F, 9V, and 14 were the most frequently isolated. We compared 53 clinical isolates (14 type 9V, 26 type 23F, and 13 type 14) by analysis of chromosomal macrorestriction patterns and DNA restriction patterns of the penicillin-binding protein (PBP) genes pbp 2b, pbp 2x, and pbp 1a. All 9V isolates originated from the same clone. Five 23F clones were distinguished, the largest of which comprised 20 isolates. The main type 14 clone comprised nine isolates; three other type 14 strains were closely related to the 9V clone, probably by horizontal transfer of capsular biosynthesis genes. Most 23F and type 14 isolates shared the same PBP gene restriction patterns as the 9V clone, suggesting horizontal transfer of altered PBP genes.